Design and evaluation of a mobile application for enhancing farm management and performance assessment in fattening beef cattle (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to develop a mobile application (app) specifically designed for enhancing farm management and performance assessment in fattening beef cattle. Materials and Methods: The development process followed a user-centered design approach, which involved focus group discussions and key informant interviews with 20 participants to design content and features. The app was developed for both mobile and web platforms. After the prototype and launch of the app, the system usability scale (SUS) and user satisfaction were assessed. Results: The assessment findings identify the specific expected functions in the app, with the farm accounting records function being the most desired feature among users, followed by production analysis, production records, and resource inventory. The mean SUS score was calculated to be 75.17, indicating a qualitative assessment of “Good.” The assessment of user satisfaction indicated that the mean satisfaction score for all participants was 4.26, suggesting a high level of satisfaction and a favorable perception of the app. Conclusion: This app provides an alternative way to record farm activity, suggest feed and feeding schedules, and provide financial management tools designed explicitly for small-scale beef cattle farmers.Adv. Vet. Anim. Res., 11(1): 203-211, March 2024http://doi.org/10.5455/javar.2024.k766